The Function of Class Management in The Improving Effectiveness of Learning Aqidah in MTs Al-Hidayah Betoyokauman Gresik - Asrori Asrori (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
The success of teaching in the sense of achieving teaching objectives, it really depends on the ability of the class. Classes that can create situations to enable students to learn well are a starting point for teaching success. And students can learn well in a normal atmosphere without pressure and in conditions that are stimulating to learn. They need guidance and assistance to understand teaching materials in various learning activities. In learning activities, students need something that allows them to communicate well with the teacher, with friends and with the surrounding environment. This type of research used in this research is a case study. In this case, explaining that a case study is a research conducted on a unified system. This unit can be like a program, activity, event, or group of individuals who are bound by a certain place, time or bond. In short, a case study is a research that is directed to collect data, take meaning, gain understanding of the case. From the results of the author's research at MTs Al-Hidayah Betoyo Kauman Gresik regarding